Shell and Tube Heat Exchanger Design: Utilization of Wasted Energy in Air Conditioning Systems - Apriandi MS, Nanang; Herlambang, Yusuf Dewantoro; Alfauzi, Abdul Syukur; Lee, Shun-Ching (Politeknik Negeri Semarang, 2023)
This research aims to design a simple Shell and Tube (one pass) heat exchanger for applications in recovering wasted heat from air conditioning systems in the hospitality industry. The Tubular Exchanger Manufacturers Association (TEMA) standard is used as a reference in the design of heat exchangers in order to obtain the dimensional specifications of the device. In addition, mathematical calculations based on the technical properties of the working fluid are carried out with the help of the Microsoft Excel application to obtain values from other parameters in the design. The results showed that the designed heat exchanger met the standards in terms of device effectiveness. The heat exchanger has 152 tubes with an effective value of more than 90% with an impurity factor of 0.014. A high tool effectiveness value indicates a good heat exchanger performance. The results of this planning and design are expected to be a reference in designing an effective heat exchanger with high reliability.